Special Features of the Crime’s Subject Under the Article 330 of the Criminal Code of Ukraine - V. Yu. Boichuk (Law and Safety, 2019)
On the basis of the analysis of criminal and legal literature, certain provisions of the Criminal Code of Ukraine and court practice of their application, the author has determined that the description of special features of the crime’s subject through the construction of “in connection with the performance of official duties” used by the legislator in the disposition of the Art. 330 of the Criminal Code of Ukraine indicates the identity of the subject to the category of officials. At the same time, taking into account the dualism of criminal and legal approaches to the definition of the term of “an official” in the descriptions of a victim and the crime’s subject, the author has emphasized on the application of the more narrow concept laid down in Part 3 of the Art. 18 of the Criminal Code of Ukraine and the Resolution of the Plenum of the Supreme Court of Ukraine dated from April 26, 2002 No. 5 “On judicial practice in cases of bribery”.